2022
DOI: 10.1111/bjh.18145
|View full text |Cite
|
Sign up to set email alerts
|

Platelet degranulation and bleeding phenotype in a large cohort of Von Willebrand disease patients

Abstract: Summary Von Willebrand disease (VWD) is a bleeding disorder caused by quantitative (type 1 or 3) or qualitative (type 2A/2B/2M/2N) defects of circulating von Willebrand factor (VWF). Circulating VWF levels not always fully explain bleeding phenotypes, suggesting a role for alternative factors, like platelets. Here, we investigated platelet factor 4 (PF4) in a large cohort of patients with VWD. PF4 levels were lower in type 2B and current bleeding phenotype was significantly associated with higher PF4 levels, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, circulating VWF levels do not always fully explain bleeding phenotypes, suggesting a role for alternative factors, like platelets. A positive correlation between PF4 and VWF : Ag levels in type 2A VWD patients (r = 0.229, p = 0.010) was found, which might indicate a similar interaction in vivo (53). Low plasma ADAMTS13 activity or reduced ratio of ADAMTS13 activity to VWF antigen or activity was found prevalent in patients with suspected HIT (54), which suggests that PF4 may reduce VWF cleavage by inhibiting ADAMTS13 activity.…”
Section: Potential Role Of the Pf4-vwf Complex In Immune-associated T...mentioning
confidence: 77%
“…However, circulating VWF levels do not always fully explain bleeding phenotypes, suggesting a role for alternative factors, like platelets. A positive correlation between PF4 and VWF : Ag levels in type 2A VWD patients (r = 0.229, p = 0.010) was found, which might indicate a similar interaction in vivo (53). Low plasma ADAMTS13 activity or reduced ratio of ADAMTS13 activity to VWF antigen or activity was found prevalent in patients with suspected HIT (54), which suggests that PF4 may reduce VWF cleavage by inhibiting ADAMTS13 activity.…”
Section: Potential Role Of the Pf4-vwf Complex In Immune-associated T...mentioning
confidence: 77%
“…We have recently shown that PF4 levels in plasma are positively correlated with current severity of bleeding phenotype in VWD type 1 patients [52]. PF4 is a chemokine that is mainly produced by megakaryocytes and stored in platelet alpha-granules, which means that systemic PF4 levels are reflective of platelet degranulation.…”
Section: Discussionmentioning
confidence: 99%